The Role Of Bale Sarasehan In The Maintenance And Preservation Of Local Cultural Identity in Cireundeu Traditional Village - Turmudzi, Bassya Saquf; Fariz, Muhammad Al; Putri, Sarah Salmadha; Al Aziz, Balya Ramdifa; Martana, Salmon Priaji (Waca Cipta Ruang, 2024)
Cireundeu traditional village is one of the traditional villages in West Java that still keeping its noble values applied to the community from generation to generation. These noble values are also applied through one of its architectural cultural products, Bale Sarasehan. Its existence is very important in terms of functional and symbolic aspects. Functionally, Bale Sarasehan acts as a gathering place for the community to carry out various traditional activities that can strengthen social ties and cultural values inherent in their identity, such as religious ceremonies, traditional art performances, a space to transmit and pass on cultural knowledge to the younger generation. While the building is symbolically conveyed through its architectural form and also the use of materials in its structure, it also has a connotative meaning or message about the life teachings of its community. This research uses a limited fieldwork method with a qualitative approach and collects data through observation, interviews and documentary studies. Through this research, it is expected to gain a better understanding of the role of Bale Sarasehan, which can contribute to the sustainability of the maintenance and preservation of local wisdom as a local cultural identity in Cireundeu Traditional Village. Cireundeu traditional village is one of the traditional villages in West Java that still keeping its noble values applied to the community from generation to generation. These noble values are also applied through one of its architectural cultural products, Bale Sarasehan. Its existence is very important in terms of functional and symbolic aspects. Functionally, Bale Sarasehan acts as a gathering place for the community to carry out various traditional activities that can strengthen social ties and cultural values inherent in their identity, such as religious ceremonies, traditional art performances, a space to transmit and pass on cultural knowledge to the younger generation. While the building is symbolically conveyed through its architectural form and also the use of materials in its structure, it also has a connotative meaning or message about the life teachings of its community. This research uses a limited fieldwork method with a qualitative approach and collects data through observation, interviews and documentary studies. Through this research, it is expected to gain a better understanding of the role of Bale Sarasehan, which can contribute to the sustainability of the maintenance and preservation of local wisdom as a local cultural identity in Cireundeu Traditional Village.